Therapeutic Modulation of Autophagy in Leukaemia and Lymphoma - Mojgan Djavaheri-Mergny; Sylvie Giuriato; Mario P. Tschan; Magali Humbert (Cells, 2019)
Haematopoiesis is a tightly orchestrated process where a pool of hematopoietic stem and progenitor cells (HSPCs) with high self-renewal potential can give rise to both lymphoid and myeloid lineages. The HSPCs pool is reduced with ageing resulting in few HSPC clones maintaining haematopoiesis thereby reducing blood cell diversity, a phenomenon called clonal haematopoiesis. Clonal expansion of HSPCs carrying specific genetic mutations leads to increased risk for haematological malignancies. Therefore, it comes as no surprise that hematopoietic tumours develop in higher frequency in elderly people. Unfortunately, elderly patients with leukaemia or lymphoma still have an unsatisfactory prognosis compared to younger ones highlighting the need to develop more efficient therapies for this group of patients. Growing evidence indicates that macroautophagy (hereafter referred to as autophagy) is essential for health and longevity. This review is focusing on the role of autophagy in normal haematopoiesis as well as in leukaemia and lymphoma development. Attenuated autophagy may support early hematopoietic neoplasia whereas activation of autophagy in later stages of tumour development and in response to a variety of therapies rather triggers a pro-tumoral response. Novel insights into the role of autophagy in haematopoiesis will be discussed in light of designing new autophagy modulating therapies in hematopoietic cancers.